2011
DOI: 10.1007/s11426-011-4222-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and thermodynamic properties of binary self-condensing vinyl polymerization

Abstract: The thermodynamic properties of a binary self-condensing vinyl polymerization system consisting of monomers and inimers are investigated by the principle of statistical mechanics. In detail, in terms of two types of canonical partition functions constructed from different viewpoints, the equilibrium free energy, the law of mass action and the size distribution of hyperbranched polymers are obtained. As an application, the specific heat, equation of state and isothermal compressibility concerning the polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Making use of the equation of state in Eq. (26) together with the law of mass action given by Eqs. (15) and (18), the isothermal compressibility  T can be carried out as:…”
Section: Several Thermodynamical Properties Of the Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Making use of the equation of state in Eq. (26) together with the law of mass action given by Eqs. (15) and (18), the isothermal compressibility  T can be carried out as:…”
Section: Several Thermodynamical Properties Of the Systemmentioning
confidence: 99%
“…Recently, the method of statistical mechanics has been applied to study a series of SCVP systems [25][26][27][28], and the equilibrium free energy and law of mass action were given in their explicit expressions. Furthermore, some average physical quantities such as polymeric moments and mean square radius of gyration can be correlated with thermodynamic quantities of the system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the method of statistical mechanics becomes a powerful tool in the investigation of some average properties of polymers. Recently, we have demonstrated that the statistical mechanical method can be employed to study several SCVP systems [23][24][25]. As a consequence, the SDF, number-, weight-, and z-average molecular weights, polydispersity index, and the degree of branching can be evaluated.…”
Section: Introductionmentioning
confidence: 99%